METHODOLOGY, IDEOLOGY AND PEDAGOGY OF AFRICAN ART primitive to metamodern. - Okediji, Moyosore B. (Moyosore Benjamin) ([S.l.] : ROUTLEDGE, 2024)
This edited volume, including contributions from scholars with different areas of specialization, investigates a broad range of methodologies, ideologies and pedagogies focusing on the study of the art of Africa, using theoretical reflections and applications from primitivism to metamodernism. Chapters break the externally imposed boundaries of Africa-related works beyond the conventional fragments of traditional, contemporary and diaspora. The contributions are significantly broad in their methodologies, ideologies and pedagogical coverage; yet, they all address various aspects of African artistic creativity, demonstrating the possibilities for analytical experiments that art history presents to scholars of the discipline today. The Iwa (character) of each approach is unique; nevertheless, each is useful toward a fuller understanding of African art studies as an independent aspect of art historical research that is a branch or bud of the larger family of art history. The volume respects, highlights and celebrates the distinctiveness of each methodical approach, recognizing its contribution to the overall character or Iwa of African art studies. The book will be of interest to students in undergraduate or graduate, intermediate or advanced courses as well as scholars in art history and African studies.
Keywords: Arts -- Africa; ART / African; ART / Criticism